„Blind football” i (nie)widoczna integracja (nie)widocznych piłkarzy - Kasprzak, Tomasz (Kultura-Społeczeństwo-Edukacja, 2021)
“Blind football” was initiated in the last century. What has significantly contributed to its development are newly established organizations, the primary goal of which was to manage various forms of activating people with visual impairment. Popularisation of “blind football” is a long-term, complicated process, in which a plethora of factors are involved. The aim of this article is to reflect on “blind football”, especially on the problems with spreading it. Most of all, the article is an attempt to define the mechanism of the functioning of “blind football” in the sphere of meanings of contemporary culture.